Kinematics and Kinetics of the Lower Limb In Uphill and Downhill Running: A Comparison of Forefoot Strike and Rearfoot Strike Runners - Kowalski, Erik (Université d'Ottawa / University of Ottawa, 2015)
his study investigated the lower limb biomechanics during downhill and uphill running in habitual forefoot strike and habitual rearfoot strike runners. Fifteen habitual forefoot strike and fifteen habitual rearfoot strike recreational male runners ran at 3 m/s ± 5% during level, uphill and downhill overground running on a ramp mounted at 6° and 9°. Results showed that hill running had similar impacts on joint angles in rearfoot strike and forefoot strike runners, causing a decrease in hip flexion at initial contact during downhill running, an increase in knee flexion angle at initial contact during uphill running and a decrease in peak hip flexion angle. In addition to differences in ankle joint angle due to landing pattern difference between rearfoot strike and forefoot strike runners, forefoot strike runners had a more flexed hip angle during downhill running. Forefoot strike runners had an absent impact peak in all running conditions, while the impact peaks only decreased during the uphill conditions in rearfoot strike runners. Active peaks decreased during the downhill conditions in forefoot strike runners while active loading rates increased during downhill conditions in rearfoot strike runners. Compared to the level condition, parallel braking peaks were larger during downhill conditions and parallel propulsive peaks were larger during uphill conditions. Peak hip flexion moment was significantly greater while peak knee flexion moment was significantly lower in both groups during the downhill 9° condition. Forefoot strike runners had larger peak plantar flexion moments and peak ankle power absorption compared to rearfoot strike runners during all conditions. Forefoot strike runners had decreased peak power absorption at the knee joint during downhill and level running conditions. Combined with previous biomechanics studies, our findings of no impact peak in forefoot strike runners suggests that this landing pattern may have potential in reducing overuse running injuries. Forefoot strike running reduces loading at the knee joint and can be used as an effective strategy to reduce stress at the knee joint experienced with rearfoot strike running.
Keywords: Biomechanics; Incline; Slope; Decline